Effects of training in the use of Toulmin's model on ESL students' argumentative writing and critical thinking ability - Zainuddin, Siti Zaidah; Rafik-Galea, Shameem (Malaysian Association of Modern Languages, 2016)
A persistent concern in many Asian schools today is the quality of students’ thought processes. Critical-thinking skills are important to meet the present global expectations and challenges. Often, students find it difficult to think critically and need a great deal of structured guidance when completing tasks which require higher-order thinking skills, such as argumentative writing. Though important, argumentative writing is a challenging mode of discourse not only for L2 students, but also for a large majority of L1 students, because they too, think critically and reason logically. This paper presents and discusses an approach that uses the Toulmin’s model of logical reasoning, which incorporates questioning techniques to provide scaffolding for students’ argumentative writing and critical-thinking ability. This paper illustrates how students with low language ability were able to learn how to think constructively and develop appropriate critical-thinking skills for argumentative writing. Pedagogical considerations for enhancing the teaching and learning of argumentative writing for teachers and ESL practitioners alike are suggested.